2018
DOI: 10.1158/1078-0432.ccr-17-1792
|View full text |Cite
|
Sign up to set email alerts
|

NY-ESO-1 Vaccination in Combination with Decitabine Induces Antigen-Specific T-lymphocyte Responses in Patients with Myelodysplastic Syndrome

Abstract: Treatment options are limited for patients with high-risk myelodysplastic syndrome (MDS). The azanucleosides, azacitidine and decitabine, are first-line therapy for MDS that induce promoter demethylation and gene expression of the highly immunogenic tumor antigen NY-ESO-1. We demonstrated that patients with acute myeloid leukemia (AML) receiving decitabine exhibit induction of NY-ESO-1 expression in circulating blasts. We hypothesized that vaccinating against NY-ESO-1 in patients with MDS receiving decitabine … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 51 publications
1
75
0
Order By: Relevance
“…Decitabine, also known as 5-aza-2 0 -deoxycytidine, is an FDA-approved hypomethylating agent that has shown a unique ability in facilitating an immune response against malignancies by elevating the expression of some given epitopes and consequently provided targets for specific immune attack (32,33), as well as its function in directly suppressing the proliferation of cancer cells (34,35). Epigenetic hypomethylating treatment has occupied a position in the treatment against leukemias (35,36), but its role in osteosarcoma treatment remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Decitabine, also known as 5-aza-2 0 -deoxycytidine, is an FDA-approved hypomethylating agent that has shown a unique ability in facilitating an immune response against malignancies by elevating the expression of some given epitopes and consequently provided targets for specific immune attack (32,33), as well as its function in directly suppressing the proliferation of cancer cells (34,35). Epigenetic hypomethylating treatment has occupied a position in the treatment against leukemias (35,36), but its role in osteosarcoma treatment remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…CDX-1401,a vaccine featuring the fusion protein of CD205(DEC-205), a marker on dendritic cells, and cancer-testis antigen 1 (CTAG1 or NY-ESO-1), was shown to effectively induce cytotoxic response from T cells when examined ex vivo and has recently concluded phase I with no clinical outcomes reported to date. [81] Another vaccine target includes the PR1 peptide, an HLA-A2 restricted peptide on myeloid leukemia cells, Initially developed in 2008, the first phase I trial displayed both safety and efficacy of the PR1 vaccine. [82] Last year another phase I/II trial also demonstrated robust immune response (53% patients had at least doubled PR1-specific cytotoxic T cells (CTLs)) and objective clinical response (24% patients had complete, partial or hematological improvement) (NCT00004918).…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] In the setting of myelodysplastic syndrome, the combination of vaccination against NY-ESO-1 and decitabine resulted in an increased antigen-specific immune response. 26 In our hands, the combination of next-generation DC vaccination with 5azacytidine resulted in a striking increase in local and systemic immune responses. This translated into a temporary MRD conversion in a single patient.…”
Section: Discussionmentioning
confidence: 61%